Ultra‐broadband linearly polarisation manipulation metamaterial. Issue 23 (1st November 2014) - Li, Yongfeng; Zhang, Jieqiu; Qu, Shaobo; Wang, Jiafu; Zheng, Lin; Zhang, Anxue; Xu, Zhuo
Abstract : The polarisation state is a basic property of electromagnetic waves. In this reported work, high efficiency, ultra‐broadband polarisation manipulation is achieved using an ultra‐thin metamaterial composed of three metasurfaces spaced by dielectric layers. It is found that the proposed metamaterial can achieve a very high conversion efficiency with cross‐polarisation transmission >96% and co‐polarisation reflection over 99% covering the range from 9.6 to 28 GHz. The simulated results are very consistent with the experimental measurements.